Graphics 3 : Angebotskatalog internationaler Druckgraphik 1960 - 1984 Edition Schellmann & Klüser München. - Schellmann & Klüser, München; Schellmann & Klüser, New York (München : Verlag Schellmann & Klüser, 1984)
Albers, Joseph ; Alfano, Carlo ; Arakawa, Shusaku ; Arman ; D'Arcangelo, Allan ; Baldessari, John ; Baselitz, Georg ; Basquiat, Jean Michel ; Beuys, Joseph ; Bohrmann, Karl ; Borofsky, Jonathan ; Brauntuch, Troy ; Brus, Günter ; Chia, Sandro ; Christo ; Clemente, Francesco ; Close, Chuck ; Cucchi, Enzo ; Dibbets, Jan ; Disler, Martin ; Erben, Ulrich ; Fischl, Eric ; Francis, Sam ; Gitlin, Michael ; Gilbert & George ; Goldstein, Jack ; Graubner, Gotthard ; Hamilton, Richard ; Haring, Keith ; Hockney, David ; Hutchinson, Peter ; Indiana, Robert ; Immendorf, Jörg ; Johns, Jasper ; Jones, Allen ; Judd, Don ; Kienholz, Edward ; Kounellis, Jannis ; LeWitt, Sol ; Lichtenstein, Roy ; Longo, Robert ; Lüpertz, Markus ; Mangold, Robert ; De Maria, Nicola ; Merz, Mario ; Merz, Gerhard ; Nestler, Wolfgang ; Nauman, Bruce ; Oldenburg, Claes ; Oppenheim, Dennis ; Paladino, Mimmo ; Paik, Nam June ; Palermo ; Panamarenko ; Penck, A.R. ; Pistoletto, Michelangelo ; Rainer, Arnulf ; Rauschenberg, Robert ; Richter, Gerhard ; Rivers, Larry ; Rosenquist, James ; Rot, Diter ; Rückriem, Ulrich ; Salle, David ; Schifano, Mario ; Schnabel, Julian ; Serra, Richard ; Spoerri, Daniel ; Stella, Frank ; Tatafiore, Ernesto ; Tapies, Antoni ; Twombly, Cy ; Warhol, Andy ; Winnewisser, Rolf
Duits & Engels
boek